Effect of buffer composition on the background activities of choline kinase - Yong, Lee Shin (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
Choline kinase has become one of the popular enzymes that has recently been studied extensively as it functions to catalyze the phosphorylation of choline to form phosphocholine in the presence of ATP and magnesium. Choline kinase exists in three isoforms which are CKal, CKa2 and CKp encoded by two separate genes, Chka and Chkfl. Pyruvate kinase-lactate dehydrogenase (PK.-LDH) coupled enzymatic assay was used to determine the activities for hCKa2 and hCKp. Background activity was the activity observed before choline was added into the reaction. The existence of background activity in enzymatic assay of hCKa2 and hCK.p affects the accuracy of measurement for choline kinase. Thus, different buffer systems at pH 8.5 were used to compare the effect of these buffers towards the background activity of hCKa2 and hCKp. The aim of this study was to reduce the background activity of choline kinase by using different buffer systems (pH 8.5) for enzymatic assay. The buffers tested for enzymatic assay were borate, glycine-NaOH, HEPES, Tris-acetate, Tris-maleate and tricine. Kinetic parameters for hCKa2 and hCKp were determined with buffers that removed the background activity of the enzymes. The buffers that abolished the background activity of choline kinase were glycine-NaOH, HEPES and tricine buffers. The highest Vmax for hCKa2 of 87.41 pmol/min/mg with choline as the substrate was obtained in tricine buffer, while HEPES buffer gave the highest Vmax of 41.60 pmol/min/mg for hCKp. With ethanolamine as substrate, the highest Vmax for both hCKa2 and hCKp were obtained in tricine buffer with the values of 37.71 and 13.86 pmol/min/mg respectively. In conclusion, glycine-NaOH, HEPES and tricine buffers were able to remove the background activities of the hCKa2 and hCKp. The activity level of these enzymes were also dependent on the buffer system used in enzymatic assay.